1977
DOI: 10.1159/000180761
|View full text |Cite
|
Sign up to set email alerts
|

Androgens in the Anaemia of Chronic Renal Failure

Abstract: Plasma levels of testosterone-like substances (TLS) were depressed in seven patients with chronic renal failure. Intramuscular testosterone (as Sustanon 250® once a week) elevated plasma TLS levels to above normal throughout the week with an initial high peak. Sublingual testosterone produced a high but brief peak in TLS. Results were similar in renal failure patients and normal controls. A controlled trial of weekly Sustanon 250 in 24 regular dialysis patients produced a significant increase in haemoglobin fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
5
0
1
Order By: Relevance
“…It is the free fraction which is considered to be the active moiety. The tendency towards higher SHBG levels in our uraemic subjects may merely reflect their hypogonadal state as low levels of testosterone are known to be associated with high SHBG concentrations which are lowered by administration of androgen (Anderson 1972 Trials of androgen supplementation in uraemia have been attempted but the main aim has been to increase haemoglobin levels (Hendler et al 1974;Hartitzsch et al 1977). Replacement therapy with testosterone has not been widely employed because of the lack of an orally active preparation.…”
Section: Discussionmentioning
confidence: 99%
“…It is the free fraction which is considered to be the active moiety. The tendency towards higher SHBG levels in our uraemic subjects may merely reflect their hypogonadal state as low levels of testosterone are known to be associated with high SHBG concentrations which are lowered by administration of androgen (Anderson 1972 Trials of androgen supplementation in uraemia have been attempted but the main aim has been to increase haemoglobin levels (Hendler et al 1974;Hartitzsch et al 1977). Replacement therapy with testosterone has not been widely employed because of the lack of an orally active preparation.…”
Section: Discussionmentioning
confidence: 99%
“…T treatment for anemia in patients with renal failure was a common medication before synthetic erythropoetin was available [50]. T probably acts directly on bone marrow at the level of polychromatophylic erythroblasts and enhances the synthesis of ribosomal RNA or its precursors and stimulates a nuclear ribonuclease.…”
Section: Erythropoeisismentioning
confidence: 99%
“…von‐Hartitzsch et al. reported similar results on hemoglobin levels in 24 patients on HD. In addition, testosterone enanthate treatment (1 g/month) normalized hemoglobin values and replenished bone marrow iron stores .…”
Section: Testosterone and Comorbiditymentioning
confidence: 63%
“…Shaldon et al (98) reported an increase in hemoglobin levels after intramuscular administration of testosterone (250-500 mg weekly) in 25 patients on HD. von-Hartitzsch et al (99) reported similar results on hemoglobin levels in 24 patients on HD. In addition, testosterone enanthate treatment (1 g/month) normalized hemoglobin values and replenished bone marrow iron stores (100).…”
Section: Testosterone and Anemiamentioning
confidence: 68%